Techno-economic optimization of hybrid power systems for sustainable energy in remote communities of Iraq - Mohammed A. Qasim; Salam J. Yaqoob; Mohit Bajaj; Vojtech Blazek; Adel A. Obed (Results in Engineering)
This study investigates the potential of hybrid power systems to provide sustainable and cost-effective energy solutions for remote communities in Iraq. Iraq primarily relies on fossil fuels for electricity generation, despite possessing significant untapped renewable energy potential. This research evaluates the techno-economic and environmental performance of a hybrid power system combining photovoltaic (PV) arrays, wind turbines (WT), battery energy storage systems (BESS), and diesel generators (DG) for remote areas, using Baghdad as a case study. Using HOMER Pro software, five optimized configurations were modeled and analyzed in terms of energy output, levelized cost of energy (LCOE), net present cost (NPC), and carbon dioxide emissions (CO2). The results demonstrate that the PV/WT/BESS/DG configuration is the optimal solution, generating an annual energy output of 90.113 MWh, of which 71.7 % (64.652 MWh/year) is contributed by the PV arrays, 27.8 % (25.033 MWh/year) by wind turbines, and only 0.475 % (0.428 MWh/year) by diesel generators. Moreover, the economic analysis reveals that the optimal hybrid configuration achieves the lowest LCOE of $0.0521 per kWh and an NPC of $40,681. Furthermore, this system configuration reduces CO2 emissions to 426.337 kg/year, significantly lower than the emissions of alternative configurations such as the PV/BESS/DG system, which emits 33,384 kg/year. Finally, this research presents a realistic framework for the implementation of renewable energy systems in distant parts of Iraq, delivering a scalable, economically feasible, and ecologically sustainable approach to address increasing energy needs while reducing dependence on fossil fuels.